Three-Dimensional Optical Coherence Tomography Imaging For Glaucoma Associated With Boston Keratoprosthesis Type I and II. Issue 8 (August 2019) - Khoueir, Ziad; Jassim, Firas; Braaf, Boy; Poon, Linda Yi-Chieh; Tsikata, Edem; Chodosh, James; Dohlman, Claes H.; Vakoc, Benjamin J.; Bouma, Brett E.; de Boer, Johannes F.; Chen, Teresa C.
Abstract : Precis: Three-dimensional (3D) spectral domain optical coherence tomography (OCT) volume scans of the optic nerve head (ONH) and the peripapillary area are useful in the management of glaucoma in patients with a type I or II Boston Keratoprosthesis (KPro). Purpose: The purpose of this study was to report the use of spectral domain OCT in the management of glaucoma in patients with a type I or II Boston KPro. Materials and Methods: This study is an observational case series. Four consecutive patients with KPro implants were referred for glaucoma evaluation. A comprehensive eye examination was performed which included disc photography, visual field testing, and high-density spectral domain OCT volume scans of the ONH and the peripapillary area. 2D and 3D parameters were calculated using custom-designed segmentation algorithms developed for glaucoma management. Results: Spectral domain OCT parameters provided useful information in the diagnosis and management of 4 KPro patients. OCT parameters which can be used in KPro patients included 2D retinal nerve fiber layer (RNFL) thickness, 3D peripapillary RNFL volume, 3D peripapillary retinal thickness and volume, 3D cup volume, and 3D neuroretinal rim thickness and volume. In 3 of 4 cases where the traditional 2D RNFL thickness scan was limited by artifacts, 3D spectral domain OCT volume scans provided useful quantitative objective measurements of the ONH and peripapillary region. Therefore, 3D parameters derived from high-density volume scans as well as radial scans of the ONH can be used to overcome the limitations and artifacts associated with 2D RNFL thickness scans. Conclusions: Spectral domain OCT volume scans offer the possibility to enhance the evaluation of KPro patients with glaucoma by using both 2D and 3D diagnostic parameters that are easily obtained in a clinic setting.